1997
DOI: 10.1046/j.1365-201x.1997.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ingested fluid volume on physiological responses during prolonged exercise

Abstract: The effect of different rates of fluid ingestion on heart rate, rectal temperature, plasma electrolytes, hormones and performance was examined during prolonged strenuous exercise conducted at 21 degrees C. Seven well-trained males (24 +/- 1 yr; 68.6 +/- 2.9 kg; VO2 peak = 4.69 +/- 0.17 L min-1; mean +/- SEM) cycled for 2 h at 69 +/- 1% VO2 peak while receiving either no fluid replacement (NF), a volume of water estimated to prevent body weight loss (FR-100 = 2.32 +/- 0.10 L 2 h-1) or 50% of this volume (FR-60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
3
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 24 publications
3
82
3
7
Order By: Relevance
“…The magnitude of the increase in core temperature and heart rate (McConell et al 1997) and the decline in stroke volume (Montain and Coyle 1992) noted during exercise has been shown to be related to the degree of dehydration incurred during exercise. Several studies have used an exercise performance test subsequent to exercise-induced dehydration to study the effects of dehydration on exercise performance, but the results are somewhat conflicting.…”
Section: Exercise Capacitymentioning
confidence: 98%
See 1 more Smart Citation
“…The magnitude of the increase in core temperature and heart rate (McConell et al 1997) and the decline in stroke volume (Montain and Coyle 1992) noted during exercise has been shown to be related to the degree of dehydration incurred during exercise. Several studies have used an exercise performance test subsequent to exercise-induced dehydration to study the effects of dehydration on exercise performance, but the results are somewhat conflicting.…”
Section: Exercise Capacitymentioning
confidence: 98%
“…He concluded that hypohydration of 2% or greater may be tolerated without significant effects on performance when environmental conditions are moderate (\25°C) (Robinson et al 1995;McConell et al 1997;Backx et al 2003), but that hypohydration of approximately 2% or more of body mass impairs performance and increases the risk of heat injury when environmental temperatures are high ([30°C) (Walsh et al 1994;Below et al 1995;Yoshida et al 2002). The critical point at which a performance reduction occurs is likely to be influenced by many factors, including the rate at which hypohydration is induced, the subject's core temperature and the exercise mode: there may be some advantage of a small reduction in body mass when this must be supported or carried, as in running (Sawka and Noakes 2007).…”
Section: Exercise Capacitymentioning
confidence: 98%
“…In the water and saline trials, changes in PV after 10 min of exercise were negligible and unlikely to have been of any physiological signi®cance. Others have also found no eect of electrolyte replacement on PV when their subjects drank either water or CHO plus up to 25 mEq/l Na + solutions at rates sucient to replace most of their¯uid losses during exercise (Barr et al 1991;Cade et al 1972;Greenleaf and Brock 1980;McConnel et al 1997;Powers et al 1990). Barr et al (1991) concluded that adding palatable amounts of Na + to a solution ingested of a rate sucient to replace 0.8 l á h A1¯u id losses had little eect on changes in PV and [Na + ] during 6 h of exercise in a 30°C environment.…”
Section: Discussionmentioning
confidence: 93%
“…Since rises in plasma osmolality reduce skin blood¯ow (Montain and Coyle 1992a;Nose et al 1990), it is important for athletes to drink enough¯uid to maintain their plasma osmolality in events where dehydration and thermoregulation are of primary concern (Coyle and Hamilton 1990;Nadel et al 1990;Noakes 1993). A complete¯uid replacement with either water or carbohydrate (CHO) solutions containing up to 25 mEq Na + á l A1 maintains plasma [Na + ] and osmolality and prevents continued falls in plasma volume (PV) after the ®rst 10 min of exercise (Barr et al 1991;Cade et al 1972;Greanleaf and Brock 1980;McConnel et al 1997;Powers et al 1990). …”
Section: Introductionmentioning
confidence: 98%
“…This method will theoretically enable workers to remain euhydrated and cool by drinking cool fluids and/or ice-slurry beverages. Research has shown that dehydration caused by sweating can impair physical and cognitive performance [11], reduce maximum voluntary contraction [12], while staying euhydrated by drinking enough fluid to offset sweat losses can attenuate increases in rectal temperature (T re ) [13] [14], cardiovascular strain and perceived exertion [15] during physical activity in the heat. Likewise, research has also shown that ingestion of cool versus warm fluids during exercise attenuates the rate of rise in T re [16].…”
Section: Introductionmentioning
confidence: 99%